Petite Messe Solennelle: análise interpretativa - Lopes, Caio Guimarães Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This Project's goal is to fundament Rossini's Petite Messe Solennelle performance as a graduation project, concerning the bibliographic research, as well as describing the preparation process and the rehearsals with choral members, soloists and pianists. The project consists in two part, one of them is the text analysis (comparing different editions, historical context) and the other is the performance of the Mass integrally. A choir and pianists were weekly rehearsed for the performance of the piece to be presented in October in UNESP's Art Institute

Este trabalho tem como objetivo fundamentar a performance da Petite Messe Solennelle, de Rossini como projeto de TCC, no que diz respeito à pesquisa bibliográfica, bem como relatar o processo de preparação e ensaios com o coro, cantores solistas e instrumentistas. O trabalho consiste de duas partes, sendo uma delas a de análise do texto (comparação entre diferentes edições, contexto histórico), e a outra parte a de execução da missa de forma integral. Foi semanalmente ensaiado um coro e instrumentistas para a execução da peça a ser apresentada em outubro no próprio Instituto de Artes da UNESP
Keywords: Rossini, Gioacchino 1792-1868 Petite Messe Solennelle; Missa (Musica); Ópera; Canto coral; Concertos; Música - Execução; Mass (Music)